2016
DOI: 10.1016/j.celrep.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Hypomethylation and Expression Is Conserved in Mouse Chronic Lymphocytic Leukemia Induced by Decreased or Inactivated Dnmt3a

Abstract: SUMMARY DNA methyltransferase 3a (DNMT3A) catalyzes the formation of 5-methyl-cytosine in mammalian genomic DNA and it is frequently mutated in human hematologic malignancies. Bi-allelic loss of Dnmt3a in mice results in leukemia and lymphoma, including chronic lymphocytic leukemia (CLL). Here we investigate whether mono-allelic loss of Dnmt3a is sufficient to induce disease. We show that by 16 months of age, 65% of Dnmt3a+/− mice develop a CLL-like disease and 15% of mice develop non-malignant myeloproliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 35 publications
4
46
0
Order By: Relevance
“…That CD34 1 stem cells are the apex of CLL pathogenesis is further supported by a mouse model with long-term conditional inactivation of DNMT3A in HSCs, which develop a CLL phenotype. 100 As mentioned, HCL patients have been found to harbor the BRAFV600E mutation in both mature lymphocytes, B-cell precursors, and human CD34 1 stem cells. 53 The same study transplanted highly purified stem cells from an untreated HCL patient into mice.…”
Section: Animal Models Of Malignant Lymphoid Stem Cellsmentioning
confidence: 90%
“…That CD34 1 stem cells are the apex of CLL pathogenesis is further supported by a mouse model with long-term conditional inactivation of DNMT3A in HSCs, which develop a CLL phenotype. 100 As mentioned, HCL patients have been found to harbor the BRAFV600E mutation in both mature lymphocytes, B-cell precursors, and human CD34 1 stem cells. 53 The same study transplanted highly purified stem cells from an untreated HCL patient into mice.…”
Section: Animal Models Of Malignant Lymphoid Stem Cellsmentioning
confidence: 90%
“…Indeed, studies in mouse models support that mutations in DNMT1 and DNMT3A promote tumor growth of T cell lymphoma and lung cancer, respectively (78,79). A recent study identified DNMT3A as a haploinsufficient tumor suppressor in chronic lymphocytic leukemia (CLL), revealing that decreased levels of DNMT3A are sufficient for disease induction, even though with a later onset than in case of its lack in DNMT3A-deficient mice (80). Both DNMT3A +/and DNMT3A Δ/Δ CLL cells share a common set of DNA hypomethylated and overexpressed genes that were assigned to a role in cancer.…”
Section: Aberrant Dna Methylation and Cancermentioning
confidence: 99%
“…8 However, no major member of the DNA methylation control pathway was recurrently found mutated in CLL and malignant B-cell differentiation. [12][13][14][15][16] Another player in B-cell malignant development is the activationinduced cytidine deaminase (AID) gene, which encodes a cytidine deaminase and is known to initiate both class switch recombination and somatic hypermutation, 2 main mechanisms implicated in the maturation of the antibody response. AID expression is tightly regulated, and its aberrant activity has been shown to induce mutations in nonimmunoglobulin genes, thus contributing to cellular transformation.…”
Section: Introductionmentioning
confidence: 99%